Role of Social TV in the Social Network - Luengsakchai, Somkiet (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2019)
The role of television in society has evolved along with the development of communication technologies, which persuade and motivate the audience to interact with TV shows and social groups. Today there are new media alternatives that enable people to use social media technologies while simultaneously watching TV shows. The results change the role of TV in society to the role of social TV in the social network. Social TV creates a new media landscape for online consumers. This situation is interesting to the TV industry. TV production firms and advertising businesses collaborate to create TV shows. Social TV encourages the audience to watch TV while simultaneously useing social media tools (Twitter, Facebook, LINE, WhatsApp) as a second screen or backchannel. If the active audience participate and interact with TV shows, the active audience will become fans or loyal followers.